Control under times of uncertainty: the relationship between hospital competition and physician-patient disputes - Qian Yang; Jay Pan (BMC, 2017)
Abstract Background Recently, cases of medical disputes and even acts of violence toward physicians by patients in China have been escalating. It remains unknown whether competition improves the patient-physician relationship. Methods This paper analyzes the relationship between hospital competition and the probability of medical disputes occurrence according to the theory of social control. Data from all hospitals in the Sichuan province of China from 2011 to 2014 were included in the study. The fixed radius approach with GIS information was employed to define hospital market, and the differences in competition over time and across regions were utilized. Our analysis is based on the fixed effect estimation, which accounts for the time-invariant unobserved heterogeneity among hospitals. Results We found an inversed U-shaped relationship between HHI and the likelihood of medical disputes. As beneath either situation of monopoly or full competition, the burst of physician-patient dispute was downward into a valley, but it rises and then falls again with the increase of HHI, it reached the peak at the typical semi-market hospital competition structure. Conclusions Our results highlight the probability of change in disputes occurrence with the transition of hospital competition and its psychological explanation, providing implications for China's future health reform.